50 activities for developing leaders - Hart, Lois Borland (Human Resource Development Press, 1994)
This unique volume offers ready-to-use, proven activities to introduce and develop key skills in leadership training. Each activity includes clear objectives, detailed instructions on how to run the activity, and reproducible participant materials. Activities Cover: Leadership theories; Team building; Values and beliefs; Visionary leadership; Recognition and rewards; Change and risk taking; Professional development; Mentoring. Training Objectives: Develop key leadership skills; Recognize and address skills needing further development; Identify ability to take risks and initiate change; Encourage creativity to enhance visioning skills; Build strategies for personal development. Training Methods: 16 written exercises encourage personal reflection and development; 2 role-play scenarios aid the transfer of learning from the workshop to the workplace; 14 self-assessments help participants identify their values, beliefs, and leadership style; 14 group exercises call on participants to work together toward a common goal; 4 closure activities provide an interesting way to end a training session. Time Guidelines: 16 activities take 30 minutes or less; 34 activities take between 1 and 2 hours.